Chronic Hemodialysis for Terminal Renal Failure - Shimizu, A. G. (1966)
Ten terminal uremic patients seen over the period of one and one-half years have been kept alive by repeated hemodialysis using a modification of the Seattle system, carried out for the most part by nurses and technicians. All the patients had creatinine clearance values below 5 ml./min., and blood urea nitrogen values which ranged between 156 and 453 mg. % before beginning the first dialysis. Selection was based on their ability to co-operate with and to tolerate the regimen. Nine patients were fully rehabilitated. The major complications were those related to shunt-site infections, including septicemia, bacterial endocarditis, septic arthritis, septic pulmonary embolism and mycotic aneurysm. Nevertheless, all patients except one were rehabilitated and resumed their full-time occupations and have continued to lead happy and useful lives.